KEKHUSUSAN PROSES PENYIDIKAN TINDAK PIDANA CYBER CRIME - Renni Sartika; Sepuh A.I. Siregar; Ni Putu Riyani Kartika Sari (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2020)
The existence of the internet in human life is very supportive of all forms of human activity in today's digital era. However, technological advances with the use of the internet have resulted in the emergence of cybercrime or cyber crime. In its development, cyber crime requires special handling by the police in the process of investigation. For this reason, using normative juridical research, this study will examine the specificities of the cyber crime investigation process. In general, the process is almost the same as the criminal investigation process in general, except that it is carried out by cyber units or special units that have the task of carrying out cyber crime investigations. Apart from that, investigators of cybercrime will also use other special laws such as ITE, Consumer Protection, Banking, and so on.